Decadal analysis of water level fluctuation using GIS in Jabalpur district of Madhya Pradesh - TRIVEDI, AYUSHI; GAUTAM, VINAY KUMAR (Journal of Soil and Water Conservation, 2023)
The dynamics of groundwater depends upon lithology, landforms and the geological setups. If these factors are favourable then the aquifer condition is considered good for sufficient groundwater potential. In the current study, long-term trend detection and spatiotemporal variation of groundwater levels were analysed using Geographical Information System (GIS) and performed statistical tests for the Jabalpur district Madhya Pradesh, India. The significant decrease in the groundwater level was observed in 80 % observations wells during pre-monsoon and 90% for post-monsoon season. This study represents the groundwater level fluctuation and its trends on decadal basis for 20 years i.e., 2001-2010 and 2011-2020 in Jabalpur district, Madhya Pradesh. The previous reports showed that study area has been experiencing groundwater problems for the past few years, due to overexploitation of aquifers. The results indicated that the average depth to water level during pre-monsoon season ranges from 2.04 to 14.73 m, whereas in post-monsoon season, water level ranges from 0.83 to 11.96 m. The decadal analysis depicted that the mean water level during the period of 2001-2010 was 4.53 m, which got significantly decreased during the second decade(2011-2020), was recorded 4.84 m. During 2011-2020, the depletion was assessed, which was faster as compared to the preceding decade. The analysis of the result showed, mostly decreasing trends over the time period. This declination of groundwater level may affect most of the water-dependent activities, especially the agriculture sector. Therefore, the findings of this study may assist the decision makers and authorities for sustainable management of groundwater resource.